History and hyponoia: Herodotus and Early Literary Criticism - Sammons, Benjamin (Histos, 2012)
This article addresses two problematic passages in which Herodotus discusses Homeric poetry (2.116 and 2.53). These passages may make more sense on the hypothesis that Herodotus was familiar with some of the more radical assumptions and methods of ancient literary criticism. In particular, Herodotus seeks to interpret Homeric poetry according to hyponoiai ('hidden, underlying meanings') and may have been influenced by allegorical approaches to Homer in his views on poetic invention of the gods’ attributes.